Dextran‐Coated Antiferromagnetic MnO Nanoparticles for a T1‐MRI Contrast Agent with High Colloidal Stability. (3rd February 2016) - Neves, Herbert R.; Bini, Rafael A.; Barbosa, Jeam H. O.; Salmon, Carlos E. G.; Varanda, Laudemir C.
Abstract : A simple approach to synthesize carboxymethyl dextran‐coated MnO nanoparticles (CMDex‐MnONPs) with high colloidal stability in physiological saline solutions is described here for potential applications as a magnetic resonance imaging (MRI) T 1 contrast agent. The thermal decomposition methodology is used to produce uniform MnONPs with an average size of around 20 nm, and its hydrophobic surface is modified with CMDex molecules, conferring hydrophilic properties. After CMDex coating, the nanoparticle presents high colloidal stability in concentrations ranging from 10 to 50 μg mL −1, average hydrodynamic size ( Z ‐average) of 130 nm, polydispersity degree of ≈12%, and negative surface charge in both simulated body fluid solutions and pure water with zeta‐potential of –20 and –40 mV, respectively. The CMDex‐MnONPs with 20 nm show antiferromagnetic behavior at room temperature, and the magnetic properties are found to be strongly dependent of the nanoparticle size, increasing the contribution of the ferromagnetic Mn3 O4 phase with decreasing size for nanoparticles about 3 nm. Cytotoxicity evaluation in cancerous and noncancerous cells in the range of 5.0–50.0 μg mL −1 shows low toxicity for cancerous cells and lack of the same for healthy cells lines. Related to the magnetic properties, CMDex‐MnONP presents significant r 1 relaxivity and low r 2 / r 1 relaxivity ratio. The results suggest that these nanoparticles display characteristics for potential applications as an MRI T 1 contrast agent. Abstract : The synthesis and characterization of biocompatible MnO nanoparticles coated with carboxymethyl dextran are presented; these nanoparticles show high colloidal stability in both pure water and physiological saline solution. The coated‐nanoparticle system reveals no toxicity for healthy human cells, antiferromagnetic behavior, significant r 1 relaxivity, and low r 2 / r 1 relaxivity ratio, and is thus suitable for applications as T 1 ‐weighted contrast agents for magnetic resonance imaging (MRI).